2010
DOI: 10.1016/j.ultsonch.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound with low intensity assisted the synthesis of nanocrystalline TiO2 without calcination

Abstract: A novel method has been developed for the preparation of nano-sized TiO(2) with anatase phase. Nanoparticles with diameter about 6 nm were prepared at a relatively low temperature (75 degrees C) and short time. The synthesis was carried out by the hydrolysis of titanium tetra-isopropoxide (TTIP) in the presence of water, ethanol, and dispersant under ultrasonic irradiation (500 kHz) at low intensity. The results show that variables such as water/ethanol ratio, irradiation time, and temperature have a great inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 53 publications
1
33
0
1
Order By: Relevance
“…Ghows et al . synthesized nano‐sized TiO 2 particles through the ultrasonic waves at relatively low temperature with titanium isopropoxide in acidic media. They found that the crystalline phases of TiO 2 in the resulting particles were anatase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghows et al . synthesized nano‐sized TiO 2 particles through the ultrasonic waves at relatively low temperature with titanium isopropoxide in acidic media. They found that the crystalline phases of TiO 2 in the resulting particles were anatase.…”
Section: Introductionmentioning
confidence: 99%
“…Alammar et al (13) synthesized spherical-shaped anatase nanoparticles in the ionic liquid from titanium isopropoxide by ultrasound-assisted synthesis under ambient conditions. Ghows et al (10) synthesized nano-sized TiO 2 particles through the ultrasonic waves at relatively low temperature with titanium isopropoxide in acidic media. They found that the crystalline phases of TiO 2 in the resulting particles were anatase.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of anatase crystallinity of Samples 1–3 calculated by analysis software (Mdi jade 5.0) were 98.1%, 93.7% and >99.9%, respectively. And the average grain sizes calculated by Scherrer formula were 9.9, 7.0 and 15.1 nm, respectively . The difference of crystallisation properties between Samples 1 and 2 was caused by the variation of impurities after modification.…”
Section: Results and Analysismentioning
confidence: 91%
“…And the average grain sizes calculated by Scherrer formula were 9.9, 7.0 and 15.1 nm, respectively. [14] The difference of crystallisation properties between Samples 1 and 2 was caused by the variation of impurities after modification. As is reported, impurities like PO 4 3À , SO 4 2À , Al 3þ will hinder the growth of TiO 2 grains to some extent during the calcination process.…”
Section: Xrdmentioning
confidence: 99%
“…In comparison to other phases, using anatase phase of TiO 2 nanoparticles with controlled diameters, the high homogeneity, good morphology, high surface area and porosity is very suitable to photocatalystic applications because of higher electron mobility, lower fixed dielectric and density [50][51][52] . However, thermodynamic stability is particle-size dependent and at particle diameters below 15 nm, anatase is more stable than rutile [53] .…”
Section: Equation Reactionmentioning
confidence: 99%